2022
DOI: 10.7602/jmis.2022.25.3.97
|View full text |Cite
|
Sign up to set email alerts
|

Optimal indication of single-incision laparoscopic cholecystectomy using Konyang Standard Method in benign gallbladder diseases

Abstract: Purpose:The optimal indications for single-incision laparoscopic cholecystectomy (SILC) have not yet been established. Methods:This single-center retrospective study included consecutive patients who underwent SILC between April 2010 and June 2020. Difficult surgery (DS) (conversion to multiport or open cholecystectomy, adjacent organ injury, operation time of ≥90 minutes, or estimated blood loss of ≥100 mL) and poor postoperative outcome (PPO) (postoperative hospital stay ≥ 7 days or Clavien-Dindo grade ≥ II… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…The use of SILC in patients undergoing AC remains controversial. Recently, the authors analyzed 1,402 SILC procedures and reported that SILC is not recommended for patients with grade II/III AC according to the TG18 [ 15 ]. This study only included patients who underwent SILC.…”
Section: Discussionmentioning
confidence: 99%
“…The use of SILC in patients undergoing AC remains controversial. Recently, the authors analyzed 1,402 SILC procedures and reported that SILC is not recommended for patients with grade II/III AC according to the TG18 [ 15 ]. This study only included patients who underwent SILC.…”
Section: Discussionmentioning
confidence: 99%
“…This study [ 7 ] analyzed the outcomes of SILC performed on patients with benign gallbladder disease based on a retrospective analysis of single-center cases. To determine the optimal indication of SILC, this study analyzed various factors, including operation time, estimated blood loss, adjacent organ injury, postoperative complications, and length of hospital stay, focusing on difficult surgery and poor postoperative outcome.…”
mentioning
confidence: 99%